Immigration, work and health: a Bibliographic Review of Migration between Mexico and the United States - Flynn, Michael A.; Carreón, Tania; Eggerth, Donald E.; Johnson, Antoinette I. (Trabajo Social UNAM, 2016)
It is necessary to understand that work and occupation influence the health of individuals and this influence goes beyond the dangers, risks and physical, emotional and social conditions with which people may face them. Work or occupation also has an important influence on other aspects of life which contribute to or affect the health of individuals and their families. Jobs are the main incentive for Mexican migration going to the United States. Mexican migrants suffer from the effect of physical health and chronic illnesses which tend to grow worse as they spend more and more time in the United States. The close relationship between work and immigration suggests that for many Mexicans immigration may be analogous to a profession which places them and their families in situations which may affect their physical, emotional and social health as a result of their work. Given the large number of Mexicans who emigrate for seeking jogs, it is essential that social workers take into account the physical, mental and social impacts associated with emigration when they work with migrants on the individual, family or community level, as well as at the level of the system. This paper is a bibliographic review which explores the effect of migration on the health of people who emigrate and of their families who stay behind.